New titanium (III) phosphite structure and its application as anode for lithium ion batteries. (3rd April 2020) - Lallaoui, Abdelfettah; Edfouf, Zineb; Benabdallah, Omar; Idrissi, Siham; Abd-Lefdil, Mohammed; Cherkaoui El Moursli, Fouzia
Abstract: A new titanium (III) phosphite Ti2 (HPO3 )3, has been synthesized under hydrothermal conditions. The solid-state structure of this material was solved using single-crystal X-ray diffraction. The anionic inorganic skeleton has a three-dimensional structure, which is built up by TiO6 octahedral units linked together via bridging HPO3 pseudo pyramids, giving rise to tunnels along the three crystallographic axes. This new compound displays a high thermal stability limit of 625 °C. IR and Raman spectroscopies show the vibrational modes of the (HPO3 ) 2− oxoanions. Electrochemical activity of this phase toward reversible insertion of Li ion was studied for the first time by galvanostatic charge-discharge measurements, an insertion host for reversible accommodation of Li + was observed. Highlights: A new titanium (III) phosphite has been synthesized under hydrothermal conditions. Crystalline structure contains tunnels along the three crystallographic axes. This is the first phosphite compound tested as anode material for Li-ion batteries. Ti2 (HPO3 )3 shows an insertion host for irreversible accommodation of Li + ion.